An insight into the clinical learning environment of dental institutes: a study in the twin cities of Pakistan - Muhammad, Muhammad; Ahmad, Zaina; Shahzad, Fatima; Sethi, Ahsan (Journal of the Pakistan Medical Association, 2024)
Objectives: To assess the perceptions of dental students regarding their clinical learning environment in an urban setting. Method: The descriptive, cross-sectional study was conducted from March 2020 to May 2021 after approval from the ethics review committee of Islamic International Dental College, Islamabad, Pakistan, and comprised clinical year students, house officers and postgraduate trainees from 6 dental teaching hospitals of Rawalpindi and Islamabad. Data was collected using a pre-validated instrument assessing the dental clinical learning environment. Data was analysed using SPSS 24. Results: Of the 1030 students approached, 561(54.4%) responded. Of them, 448(80%) were girls, 234(41.7%) were 3rd year students, 110(19.6%) were 4th year students, 120(21.4%) were house officers and 97(17.3%) were postgraduate trainees. Female students had a better patient attitude and were more confident in their abilities to keep up with their peers (p<0.05). The students were content with the performance of their clinical teachers, with a mean score of 70.99+/-16.0, while the lowest score of 54.67+/-22.9 was for clinical infrastructure and materials. Students of Islamabad pointed out the lack of clinical materials and maintenance of equipment but noted better research opportunities compared to their Rawalpindi counterparts (p<0.05). Conclusion: The clinical learning environment for Islamabad and Rawalpindi cities individually was good. Overall, students were satisfied with their clinical teachers, learning and training experience. Dental materials, infrastructure and maintenance factors scored the lowest. Key Words: Dental education, Dental graduate education, University hospital, Health facility environment, Clinical clerkship.